Rationality and Emotionality of Sponsorship Negotiations - Managerial Approaches to Sponsorship Decision-Making - Maximilian Stieler; Claas Christian Germelmann; Björn Walliser (Marketing Review St.Gallen, 2019)
In this article, we investigate how rationality and emotionality influence sponsorship negotiations and relationships between sponsors and sponsees. A total of 33 semi-structured interviews with sponsors, sponsees and sponsorship agencies shed light on these processes from three different perspectives. Our results indicate that managers appreciate and value emotionality inherent to sports for marketing purposes, but attempt to reduce the effect of emotions during the decision-making process.
Keywords: 650